Operability of atrial septal defect with borderline pulmonary vascular resistance index: A study in developing country - Oktavia Lilyasari; Rini Istisakinah; Rina Ariani; Budi Rahmat; Lies Dina Liastuti; Yovi Kurniawati; Hary Sakti Muliawan; Renan Sukmawan (Frontiers in Surgery, 2022)
BackgroundPulmonary arterial hypertension secondary to atrial septal defect (ASD) is an important determinant of morbidity and mortality in defect closure. We aimed to compare perioperative outcome between preoperative borderline and low pulmonary vascular resistance index (≥4 WU.m2 and <4 WU.m2, respectively) in surgical closure of secundum atrial septal defect with concomitant pulmonary arterial hypertension.Methods and resultsThis was a single-center retrospective cohort study between January 2015 and January 2020. We classified patients with low and borderline PVRI who underwent ASD closure and recorded the perioperative outcomes.ResultsWe analyzed a total of 183 patients with atrial septal defect and pulmonary arterial hypertension; 92 patients with borderline PVRI and 91 patients with low PVRI. Borderline pulmonary vascular resistance index was not associated with increased risk of postoperative mortality (p = 0.621; OR0.48, 95% CI 0.04–5.48), but associated with higher risk of overall morbidity in bivariate analysis (p = 0.002; OR3.28, 95% CI 1.5–6.72). Multivariate analysis showed positive association of borderline pulmonary vascular resistance index (p = 0.045; OR2.63, 95% CI 1.02–6.77) and preoperative tricuspid valve gradient ≥64 mmHg (p = 0.034; OR2.77, 95% CI 1.08–7.13) with overall morbidity.ConclusionThere is no difference in incidence of in-hospital mortality between preoperative borderline and low pulmonary vascular resistance index patients. However, preoperative borderline pulmonary vascular resistance index and tricuspid valve gradient ≥64 mmHg are associated with increased overall morbidity after surgical closure in secundum atrial septal defect patients with pulmonary arterial hypertension.